From response to responsibility: An academe-industry partnership on solid waste managament in the Philippines - Era, Marlon D. L. (Animo Repository, 2021)
By the late 1980s and early 1990s, a shift in environmental governance began to focus on advocates for effective environmental management by looking into communities and local institutions as important actors involved int he process of environmental governance. There emerged a new view in environmental governance by pinpointing three (3) social actors, the states, markets and the civil society (Lemos and Agrawal, 2006). Taking the cue from said representation lead to an examination of environmental governance by this author, in an attempt to take an in depth look on the roles, participation and accountability of non-state actors in the implementation of the solid waste management program. The paper is a portion of the author's dissertation project. Further, the paper took a look also into the trajectory of environmental governance, the roles and specific tasks particularly in the performance of private sector in its pursuit of corporate social responsibility. Citing a specific example for the research, the author chose a case study, Toyota Auto Parts Incorporated and the different schools in implementation of solid waste management in the City of Santa Rosa, Province of Laguna in the Philippines which explored a least studied partnership known as the social private partnerships (SPP). Making this study unique as it tackled the actual participation of non-state actors such as the academic institutions, and industries that are engaged in partnerships. The study made use of data surveys, focus group discussions and interviews to determine the strengths and weaknesses of different partnership arrangements in the implementation of solid waste management (SWM) City of Santa Rosa. The paper concludes that, successful environmental governance requires combination of partnership arrangements to promote improved incentives and accountability among non-state actors. The paper puts forward some recommendations for improvements of partnerships in environmental governance, particulalrly in the area of law, policy, education and research.